Bioenergy-livestock integration in Brazil: Unraveling potentials for energy production and climate change mitigation - Rinke Dias de Souza, Nariê [UNESP]; Palma Petrielli, Gabriel; Dourado Hernandes, Thayse Aparecida; Leduc, Sylvain; Di Fulvio, Fulvio; de Souza Henzler, Daniele; Ferreira Chagas, Mateus; Lopes Junqueira, Tassia [UNESP]; Cavalett, Otávio [UNESP] (Elsevier, 2023)
Future projections indicate an expansion for both food and energy demands, which can increase pressure on land use, while there is an urgent global need for climate change mitigation. Bioenergy is foreseen as key option to meet future energy demands and reduce greenhouse gas (GHG) emissions, however its sustainability depends on locations and regional characteristics. Simultaneously, agricultural production models that co-produce food, feed, and energy offer sustainability synergies and co-benefits, but site-specific sustainability assessments of their large-scale implementation are missing. This study presents a bottom-up approach to assess spatially explicit sustainability aspects of bioenergy-livestock integrated systems (BLI) in Brazil and shed light on their contribution to future energy demands, to climate change mitigation targets, and their impacts on selected ecosystem services, including bioenergy production, climate change mitigation, reduction of food competition, biodiversity conservation, and avoided deforestation. The proposed integration considers livestock intensification and use of biofuels by-products as animal feed supplement, taking advantage of synergies between these two value chains. The expansion of the BLI system in the Center-South region of Brazil produce up to 89 billion liters of ethanol, enough to meet future domestic ethanol demands from multiple shared socioeconomic pathways and generating surpluses for export. This production takes place on 16 million hectares of pastureland within the Sugarcane Agroecological Zoning, excluding the Amazon and Pantanal biomes, and biodiversity hotspots. BLI expansion mitigate up to 250 million tonnes of CO2eq and generate 15 billion dollars of profits. The best locations to maximize the selected ecosystem services are west of São Paulo, east of Mato Grosso do Sul, and the south-central region of the states of Goiás. This study may encourage the formulation of enhanced public policies for the integration of bioenergy and livestock value chains and guide a sustainable large-scale deployment of BLI systems.
Keywords: Climate change mitigation; Integrated value-chains; Land use; Life cycle assessment; Supply-chain assessment; Techno-economic analysis